Pelaksanaan Rekrutmen Tenaga Pendidik di SMP Nurul Amal Palembang. - Ibrahim, Ibrahim; Erwin, Erwin; Niswah, Choirun (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to analyze the recruitment process of educators at SMP Nurul Amal Palembang. This research employs a descriptive method with a qualitative approach. The informants in this study consist of 7 individuals, including the principal, the head of administration, teachers, and administrative staff. Data collection techniques used involve data reduction, data presentation, data verification, and conclusion drawing. The validity of the data is ensured through source triangulation, time triangulation, and technique triangulation. The research results indicate that the recruitment process of teaching staff at SMP Nurul Amal Palembang has been carried out effectively through guidance, coordination, communication, and motivation. This recruitment process includes the formation of a recruitment committee, analysis of teaching staff needs, the creation and posting of open recruitment announcements, registration of teaching staff candidates, guidance during selection, determination of the accepted teaching staff, and re-registration of the accepted teaching staff at SMP Nurul Amal Palembang. The recruitment process was conducted in accordance with the expectations of the school